2015
DOI: 10.4103/2231-0762.169211
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of serum sialic acid, fucose levels and their ratio in oral squamous cell carcinoma

Abstract: Background:Detection of cancer at the early stage is of utmost importance to decrease the morbidity and mortality of the disease. Apart from the conventional biopsy, minimally invasive methods like serum evaluation are used for screening large populations. Thus, this study aimed to estimate serum levels of sialic acid and fucose and their ratio in oral cancer patients and in healthy control group to evaluate their role in diagnosis.Materials and Methods:Serum samples were collected from 52 healthy controls (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The present study results were also in accordance with the study conducted by Chinnannavar et al ,[ 3 ] Rajpura et al ,[ 32 ] Xing et al ,[ 33 ] Shashikanth and Rao[ 34 ] Kimura et al ,[ 35 ] Wilma Delphine Silvia et al [ 36 ] and Dhakar et al ,[ 37 ] who reported a significant increase in the mean serum SA levels in OSCC compared to the normal individuals. It has been demonstrated that SA increases at the tumor cell surface, so the increase in their serum levels may be related to their increased release through increased turnover, secretion and shedding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study results were also in accordance with the study conducted by Chinnannavar et al ,[ 3 ] Rajpura et al ,[ 32 ] Xing et al ,[ 33 ] Shashikanth and Rao[ 34 ] Kimura et al ,[ 35 ] Wilma Delphine Silvia et al [ 36 ] and Dhakar et al ,[ 37 ] who reported a significant increase in the mean serum SA levels in OSCC compared to the normal individuals. It has been demonstrated that SA increases at the tumor cell surface, so the increase in their serum levels may be related to their increased release through increased turnover, secretion and shedding.…”
Section: Discussionsupporting
confidence: 92%
“…Although the oral cavity is frequently examined, 60% of intraoral carcinomas are in advanced stage at the time of detection. [ 3 ] Persistent difficulties arising in oral cancer are late diagnosis, poor response of tumor to chemotherapy, lack of reliable biomarkers for early diagnosis and posttherapeutic monitoring. [ 4 ] Therefore, early detection of oral cancer is of utmost importance for improving the survival rate and prognosis of patients with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fucose contributed to the discrimination between the skin cancer groups and HV group in PCA. Fucose is a monosaccharide that is usually present in blood as well as in tissue glycoproteins . Some reports suggested that serum fucose levels are elevated in patients with oral SCC .…”
Section: Discussionmentioning
confidence: 99%
“…Fucose is a monosaccharide that is usually present in blood as well as in tissue glycoproteins . Some reports suggested that serum fucose levels are elevated in patients with oral SCC . Although those studies targeted oral SCC, fucose could be a diagnostic biomarker in patients with SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the article titled, “Evaluation of serum sialic acid, fucose levels and their ratio in oral squamous cell carcinoma” published in pages 446-450, issue 6, vol. 5 of Journal of International Society of Preventive and Community Dentistry[ 1 ], the affiliation of the third author “Kodige Chandrashekhar Vidya” is incorrectly written as “Department of Oral Medicine and Radiology, Kalinga Institute of Dental Sciences, Bhubaneswar, Odisha” instead of “Department of Oral and Maxillofacial Surgery, Kalinga Institute of Dental Sciences, KIIT University, Bhubaneswar, Odisha”.…”
mentioning
confidence: 99%